2015
DOI: 10.1007/s11605-015-2932-y
|View full text |Cite
|
Sign up to set email alerts
|

Is It Reasonable to Treat Early Gastric Cancer with Mucosal Infiltration and Well Differentiation by Endoscopic Submucosal Resection?

Abstract: The most important factors for predicting lymph node metastasis in early gastric cancer are tumor size, pathological type, depth of invasion, and lymphatic-vascular invasion. Well-differentiated mucosal gastric cancers could be candidates for ESD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 33 publications
2
11
0
Order By: Relevance
“…Overall, the prevalence of LNM in patients with EGC of this cohort was 14.2%, which was similar to that reported in other centers in China, the United States, Brazil, France and Germany, but not in Japan and Korea in which significantly lower frequency of LNM were observed. In this study we found five independent risk factors of LNM in EGC, including a tumor size of ≥3.0 cm, deep submucosal invasion (SM2), moderate/poor tumor differentiation, LVI and tumor necrosis.…”
Section: Discussionsupporting
confidence: 89%
“…Overall, the prevalence of LNM in patients with EGC of this cohort was 14.2%, which was similar to that reported in other centers in China, the United States, Brazil, France and Germany, but not in Japan and Korea in which significantly lower frequency of LNM were observed. In this study we found five independent risk factors of LNM in EGC, including a tumor size of ≥3.0 cm, deep submucosal invasion (SM2), moderate/poor tumor differentiation, LVI and tumor necrosis.…”
Section: Discussionsupporting
confidence: 89%
“…Since we performed endoscopic resection for 64 intramucosal cancer cases with very low LNM risk in Zhongshan Hospital during the study period, LNM incidence could be 8.9% if endoscopically treated cases were included. The LNM incidence was similar to data reported by Huang (6.4%) ( 20 ), Feng (8.3%) ( 21 ) and Degiuli (10.8%) ( 22 ). There are several differences in diagnostic criterion between Western and Japanese pathologists ( 23 ).…”
Section: Discussionsupporting
confidence: 89%
“…[99][100][101] Additionally, studies reported no significant difference between the five-year survival rate of surgical resection and endoscopic resection (92.0%-97.2% vs. 93.3%-96.4%), indicating that endoscopic resection is considered curative for the aforementioned lesions with no requirement of further treatment. 95,100,[102][103][104][105][106][107][108][109] Surgical resection is the standard treatment for clinically suspected submucosal invasive gastric cancer in preoperative evaluation. However, studies analyzing pathologic results of patients who underwent gastrectomy due to preoperatively suspected submucosal invasion reported that 28.8%-43.0% of these lesions could have been treated with endoscopic resection.…”
Section: Statement G3: We Recommend Endoscopic Resection For Early Gamentioning
confidence: 99%